2018
DOI: 10.1002/anie.201711651
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Native Proteins Facilitated by Cell‐Penetrating Poly(disulfide)s

Abstract: Intracellular delivery of therapeutic proteins is highly challenging and in most cases requires chemical or genetic modifications. Herein, two complementary approaches for endocytosis-independent delivery of proteins to live mammalian cells are reported. By using either a "glycan" tag naturally derived from glycosylated proteins or a "traceless" tag that could reversibly label native lysines on non-glycosylated proteins, followed by bioorthogonal conjugation with cell-penetrating poly(disulfide)s (CPDs), we ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 35 publications
2
95
0
Order By: Relevance
“…Moreover, replacing lipoic acid with asparagusic acid monomers lead to significant loss in cellular uptake of the resultant polymers. The polymerization system has also been further applied to facilitate intracellular delivery of small‐molecule drugs and proteins …”
Section: Disulfide Bond In Polymeric Backbonementioning
confidence: 99%
“…Moreover, replacing lipoic acid with asparagusic acid monomers lead to significant loss in cellular uptake of the resultant polymers. The polymerization system has also been further applied to facilitate intracellular delivery of small‐molecule drugs and proteins …”
Section: Disulfide Bond In Polymeric Backbonementioning
confidence: 99%
“…Intact KLAK peptides are released upon applying a reductive trigger . f) Cell‐penetrating poly(disulfide)s (CPDs) mediate the intracellular uptake of protein conjugates, which undergo self‐immolative degradation and release native proteins …”
Section: Bifunctional Linkersmentioning
confidence: 99%
“…[47] f) Cell-penetrating poly(disulfide)s (CPDs)m ediate the intracellular uptake of protein conjugates, whichu ndergoself-immolative degradation and releasen ative proteins. [48] Caruso et al [47] reported the fabrication of nanoparticles directly from mitochondria-disrupting KLAK peptides by using self-immolative hetero-bifunctionall inkers (NDBC and NDEC) to cross-link peptides and eight-armed PEG-SH.T hese nanoparticles disassemble into native KLAK peptides through disulfide cleavage and self-immolative cascaded egradation (Figure 5e). In another report, Yaoe tal.…”
Section: Self-immolative (Tracelesscleavage) Hetero-bifunctional Linkersmentioning
confidence: 99%
See 1 more Smart Citation
“…acids were optimal. [41][42][43][44] After these structural and functional discoveries, the potential of CPPs has led to the development of myriadp enetrating peptides equences fort he cellulari nternalization of different payloads. [14,16] Similaru ptake properties were found for the enantiomeric TAT [49][50][51][52][53][54][55][56][57] peptidea nd in penetrating peptoidsw ith guanidiniums ide chains anchored at the nitrogen of the amide group.…”
Section: Introductionmentioning
confidence: 99%